Effects of DynEd Reading Course on Students’ Reading Proficiency and Reading Motivation - Bai Donna S. Aliman (RIRAI Publisher, 2021)
Dynamic Education (DynEd) International Inc. is a leading provider of Interactive Language Program designed to enhance learners’ English communication skills. This study aimed to determine the effect of the DynEd’s Reading course on reading proficiency and reading motivation of the students in Mindanao State University-Maguindanao during 2nd Semester of A.Y. 2017-2018. The study was conducted with the college students taking Job Enabling English Proficiency (JEEP) Start 2 courses. Sixty students were randomly selected among the eligible students to take Reading for Success course of the DynEd courseware. In this study, single group experimental with pretest and posttest design was used. The reading section of a TOEFL and Motivation for Reading Questionnaire (MRQ) by Wang and Guthrie (2004) were used as research instruments. The results showed that before DynEd Reading course was introduced, the students’ reading proficiency level was described as low. However, after the 8-week long intervention using courseware, the students’ reading proficiency level increased to intermediate level. Moreover, the students’ intrinsic and extrinsic reading motivation level before and after the intervention were all found out to be in “motivated” level. It was also found out that comparison between the pretest and posttest in reading proficiency and intrinsic reading motivation were significant. It was then concluded that the DynEd Reading course is effective in improving the reading proficiency level and intrinsic reading motivation of the college students. The result implies that DynEd courseware is an effective tool to enhance the reading skills of the students.